Mesoamerican Memory. Rain-fed corn and rituality in the region of Nevado de Toluca, State of México - Albores, Beatriz (2019)
This article approaches maize cultivation in a lake area with snow-capped volcanoes, through a production system based on rainy season and moist soil, its connection with some rituals and world conceptualizations, in relation with two Mesoamerican calendrical accounts.